Benefit of varicocelectomy in infertile men with varicocele - Awati, Shreeharsha Mallappa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Varicocelectomy does improve semen parameters and pregnancy rates in men with infertility. Various studies have shown the extent of benefit and also shown that some may not benefit. It is important to counsel the patients about the same. The present study was done to determine how much varicocelectomy is beneficial to infertile men with varicocele. Methods: A prospective observational cohort study was conducted on 25 patients undergoing varicocelectomy for infertility at St. John Medical College Hospital, Bangalore from 1st June 2013 to 31st May 2014. Clinical data, semen analysis, scrotal imaging was done and postoperatively semen analysis was done after three months. The data was analysed to find out how much was the benefit of varicocelectomy. Results: Twenty-five patients underwent varicocelectomy, all of them showed improvement of semen parameters. Fifteen of them had more than 50% of improvement. This showed that varicocelectomy is beneficial to about 60% of patients. Conclusions: Varicocelectomy is beneficial to infertile men with palpable varicocele and abnormal semen parameters.